#  1. Explaining the definition of linear equation with one variable.  2. Explaining the characteristics of linear equation with one variable. 3. Determining.

## Presentasi berjudul: " 1. Explaining the definition of linear equation with one variable.  2. Explaining the characteristics of linear equation with one variable. 3. Determining."— Transcript presentasi:

 1. Explaining the definition of linear equation with one variable.  2. Explaining the characteristics of linear equation with one variable. 3. Determining the solution of linear equation with one variable with added, substructed, multiplied and divided method.  The characters building: Discipline, respect, diligence and responsibility.

1. Have equal sign “=“ 2. Only have one variable 3. The power of variable is equal to 1

Determine the forms below, is LEOV or Not LEOV! 1) a + 5 = 7(LEOV) 2) 2b – 3 = 19(LEOV) 3) x – 2y = 15(Not LEOV) 4) 3b + 11 = b(LEOV) 5) X² + 3 = 12(Not LEOV) 6) 2 + 23 = d (LEOV) 7) 2x = 16(LEOV) 8) (¼)a – 3 = 10(LEOV) 9) 3b + b³ = 27(Not LEOV) 10) 2(x – 1) + 5(2 + x) = 5x(LEOV)

 Linear equation with one variable (LEOV) is an open sentence connected by equal sign (“=“) and only have one variable, and the power of variable is equal to 1.  General form of linear equation with one variable (LEOV) is ax + b = 0, for a ≠ 0, b is constant.  Persamaan linier satu variabel adalah Kalimat terbuka yang dihubungkan tanda sama dengan (“=“) dan hanya mempunyai satu variabel, dan pangkat variabelnya sama dengan 1.  Bentuk umum persamaan linier satu variabel adalah ax + b = 0, untuk a ≠ 0, b adalah konstanta.

1. Both sides are added by the same number. 2. Both sides are substructed by the same number. 3. Both sides are multiplied by the same number. 4. Both sides are divided by the same number.

 1. x – 7 = 3  Answer:x – 7 + 7 = 3 + 7 (both sides are added by 7) x = 10

 2.y + 5 = 12  Answer:y + 5 – 5 = 12 – 5 (both sides are substructed by 5) y = 7  3. 4a – 6 = 3a – 1  Answer:4a – 3a – 6 = 3a – 3a – 1 (both sides are substructed by 3a) a – 6 = -1 a – 6 + 6 = - 1 + 6(both sides are added by 6) a = 5

 4. 3(x - 3) = 2(x + 9)  Answer:3x - 9 = 2x + 18 3x -2x - 9 = 2x - 2x + 18(both sides are substructed by 2x) x - 9 + 9 = 18 + 9(both sides are added by 9) x = 27

1. x + 7 = 15 2. a – 4 = 6 3. 5b - 2 = 4b + 9 4. 4(x + 5) = 3(x – 6) 5. 3(2x + 7) + 5(x – 3) = 2(5x + 4)

Presentasi serupa